soln_hw6 - Solutions to Homework 6 Section 3.6 8. The...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Solutions to Homework 6 Section 3.6 8. The assumed form is Y = ( At + B ) sin(2 t )+( Ct + D ) cos(2 t ), which is appropriate for both terms appearing on the right hand side of the equation. Since none of the terms appearing in Y are solutions of the homogenous equation, we do not need to modify Y . Calculating Y 0 and Y 00 we have Y prime = A sin(2 t )+ C cos(2 t )+2( At + B ) cos(2 t ) - 2( Ct + D ) sin(2 t ) and Y 00 = - 4 C sin(2 t ) - 4( At + B ) sin(2 t ) - 4( Ct + D ) cos(2 t ). Thus Y 00 + Y = - 3 At sin(2 t ) - (3 B + 4 C ) sin(2 t ) - 3( Ct + D ) cos(2 t ). Equating like coefficients yields A = 0 , - 3 B - 4 C = 3 , - 3 C = 1, and - 3 D = 0. Hence Y ( t ) = - (5 / 9) sin(2 t ) - (1 / 3) t cos(2 t ). 18. The homogeneous solution is y c ( t ) = c 1 e - t cos(2 t )+ c 2 e - t sin(2 t ). Set Y = Ate - t cos(2 t )+ Bte - t sin(2 t ). After comparing coefficients, we get Y = te - t sin(2 t ). Hence the general so- lution is y ( t ) = c 1 e - t cos(2 t ) + c 2 e - t sin(2 t ) + te - t sin(2 t ) . (1) Invoking the initial conditions,
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 10/23/2009 for the course MATH 22B taught by Professor Hunter during the Winter '08 term at UC Davis.

Page1 / 3

soln_hw6 - Solutions to Homework 6 Section 3.6 8. The...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online